DAMPAK DANA ZAKAT, INFAQ, SEDEKAH (ZIS) TERHADAP PENGEMBANGAN USAHA MIKRO MUSTAHIK (Studi pada Usaha Mikro Binaan BAZNAS Kota Malang) - SAUFIN, NEVYLIA RACHMAWATI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Badan Amil Zakat Nasional (BAZNAS) Malang through productive distribution program, in the form KMKP program (Community Groups Productive City) provide capital assistance using Zakat funds, Infaq, sadaqah (ZIS) to micro mustahik. With the help of venture capital as well as a good empowerment is expected to have an impact on the development of micro mustahik. The purpose of this study are: (1) Knowing the mechanism of empowerment BAZNAS Malang in developing micro businesses mustahik; and (2) Examine the impact of Zakat, Infaq and Sadaqah (ZIS) towards the development of micro mustahik. The development of micro-enterprises in the study visits of the indicators profit. The approach used in this research is descriptive quantitative approach with a number of 31 respondents mustahik beneficiary productive ZIS KMKP program built BAZNAS Malang. The results showed that the mechanism of empowerment of SMEs that do BAZNAS Malang apart to provide venture capital, followed by a sustained empowerment models such as mentoring / monitoring, coaching, and training. Based on the results of multiple regression analysis using the statistical program SPSS 13, showed that the number of ZIS productive, long effort, and positive impact on the business turnover of micro enterprises mustahik advantage. Whereas other effects of ZIS BAZNAS Malang is increasing production of SMEs, create economic independence, as well as transform mustahik be muzakkiKeywords: Productive ZIS, Empowerment, Micro Enterprise Development, Business Advantage, Multiple Linear Regression.